Assessment of sequence dependent geometric distortion in contrast-enhanced MR images employed in stereotactic radiosurgery treatment planning. (25th June 2018) - Pappas, Eleftherios P; Seimenis, Ioannis; Dellios, Dimitrios; Kollias, Georgios; Lampropoulos, Kostas I; Karaiskos, Pantelis
Abstract: This work focuses on MR-related sequence dependent geometric distortions, which are associated with B 0 inhomogeneity and patient-induced distortion (susceptibility differences and chemical shift effects), in MR images used in stereotactic radiosurgery (SRS) applications. Emphasis is put on characterizing distortion at target brain areas identified by gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA) paramagnetic contrast agent uptake. A custom-made phantom for distortion detection was modified to accommodate two small cylindrical inserts, simulating small brain targets. The inserts were filled with Gd-DTPA solutions of various concentrations (0–20 mM). The phantom was scanned at 1.5 T unit using both the reversed read gradient polarity (to determine the overall distortion as reflected by the inserts centroid offset) and the field mapping (to determine B 0 inhomogeneity related distortion in the vicinity of the inserts) techniques. Post-Gd patient images involving a total of 10 brain metastases/targets were also studied using a similar methodology. For the specific imaging conditions, contrast agent presence was found to evidently affect phantom insert position, with centroid offset extending up to 0.068 mm mM −1 (0.208 ppm mM −1 ). The Gd-DTPA induced distortion in patient images was of the order of 0.5 mm for the MRI protocol used, in agreement with the phantom results. Total localization uncertainty of metastases-targets in patient images ranged from 0.35 mm to 0.87 mm, depending on target location, with an average value of 0.54 mm (2.24 ppm). This relative wide range of target localization uncertainty results from the fact that the B 0 inhomogeneity distortion vector in a specific location may add to or partly counterbalance Gd-DTPA induced distortion, thus increasing or decreasing, respectively, the total sequence dependent distortion. Although relatively small, the sequence dependent distortion in Gd-DTPA enhanced brain images can be easily taken into account for SRS treatment planning and target definition purposes by carefully inspecting both the forward and reversed polarity series.